High-strength WC-Co/Low carbon steel connected by Ni–Cr–Fe alloy through brazing for roller sleeves - Shuang Liu; Xiangpeng Chang; Yingfan Zhao; Zelin Yan; Weiping Tong (Journal of Materials Research and Technology)
Enhancing the bond strength between WC-Co and steel is crucial for broadening its applications. In this study, WC-Co was bonded to low-carbon steel (LCS) using a Ni–Fe–Cr alloy at 1180 °C in an argon atmosphere furnace. The WC-Co/LCS (WL) interface was characterized by XRD, SEM, and EPMA, revealing no cracks or pores and confirming robust metallurgical bonding. The bonded material's shear strength reached approximately 321–328 MPa, significantly exceeding that achieved with Ag–Cu–Zn–Cd, Cu–Zn, Cu–Ni–Al, Ag–Cu–Zn + Ni/Mn, and Ag–Cu–In–Ti filler materials in the welding process. EPMA analysis showed that Fe, Cr, and Ni from the Ni–Fe–Cr alloy diffused into the WC-Co over distances of approximately 802–815 μm, 803–817 μm, and 632–641 μm, respectively. Initially, WC decomposed at sharp corners to form W₂C, which subsequently reacted with Fe and Cr to form M₆C and M₇C₃. This methodology was also applied to producing roller sleeves for vertical mills, increasing their lifespan by 1.9 times.